Kierunki dostosowywania polskiego mleczarstwa do rynku Wspólnoty - Wielewska, Izabela (Changes Helping to Conform Polish Dairy Section to the EU Standards, 2005)
The process of modernization of dairy farms and dairy companies has intensified since 2004. Polish dairy products can be sold in the whole European Union, but at the same time they have to conform to EU sanitary, veterinary and technological standards.The article presents a research conducted in "Agromex" Ltd in Jabłonowo Pomorskie and Dairy Cooperative in Chojnice concerning changes helping to conform Polish dairy section to the EU standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 400-405